Specific location of penicillin-binding proteins within the cell envelope of Escherichia coli. - Barbas, J A (1986)
This communication deals with the location of penicillin-binding proteins in the cell envelope of Escherichia coli. For this purpose, bacterial cells have been broken by various procedures and their envelopes have been fractioned. To do so, inner (cytoplasmic) and outer membranes were separated by isopycnic centrifugation in sucrose gradients. Some separation methods (Osborn et al., J. Biol. Chem. 247:3962-3972, 1972; J. Smit, Y. Kamio, and H. Nikaido, J. Bacteriol. 124:942-958, 1975) revealed that penicillin-binding proteins are not exclusively located in the inner membrane. They are also found in the outer membrane (A. Rodríguez-Tébar, J. A. Barbas, and D. Vásquez, J. Bacteriol. 161:243-248, 1985). Under the milder conditions for cell rupture used in this work, an intermembrane fraction, sedimenting between the inner and outer membrane, can be recovered from the gradients. This fraction has a high content of both penicillin-binding proteins and phospholipase B activity and may correspond to the intermembrane adhesion sites (M. H. Bayer, G. P. Costello, and M. E. Bayer, J. Bacteriol. 149:758-769, 1982). We postulate that this intermembrane fraction is a labile structure that contains a high amount of all penicillin-binding proteins which are usually found in both the inner and outer membranes when the adhesion sites are destroyed by the cell breakage and fractionation procedures.